2008
DOI: 10.1007/s00423-008-0400-9
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the thoracic wall—long-term follow-up including pulmonary function tests

Abstract: Thoracic wall reconstruction provides sufficient thoracic wall stability to maintain pulmonary function, but postoperative pain and sensation disorders are considerable. However, chest wall repair can contribute to palliation and even cure after full-thickness resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 37 publications
2
56
0
8
Order By: Relevance
“…They are simple to use and usually well tolerated when completely covered by viable tissue, provide a barrier that prevents fluid and air moving between pleural and subcutaneous space and propose a scaffold for the in-growth of regenerative connective tissue colonizing their outer and inner surfaces. Some authors reported an infection rate between 10% and 25% for synthetic meshes and the needs to remove the infected mesh to resolve the problem (8,16). In these cases a Vicryl mesh could be considered due to its inert, nonantigenic, biocompatible and slowly absorbing material or a biologic mesh as like as bovine pericardium prosthesis (Figure 2), that have the same tensile strength and elasticity as those synthetic, but some proper physiologic properties of resistance to infection and contamination.…”
Section: Synthetic Biologic and Titanium Meshesmentioning
confidence: 99%
See 1 more Smart Citation
“…They are simple to use and usually well tolerated when completely covered by viable tissue, provide a barrier that prevents fluid and air moving between pleural and subcutaneous space and propose a scaffold for the in-growth of regenerative connective tissue colonizing their outer and inner surfaces. Some authors reported an infection rate between 10% and 25% for synthetic meshes and the needs to remove the infected mesh to resolve the problem (8,16). In these cases a Vicryl mesh could be considered due to its inert, nonantigenic, biocompatible and slowly absorbing material or a biologic mesh as like as bovine pericardium prosthesis (Figure 2), that have the same tensile strength and elasticity as those synthetic, but some proper physiologic properties of resistance to infection and contamination.…”
Section: Synthetic Biologic and Titanium Meshesmentioning
confidence: 99%
“…Chest wall defects generally result from resection of primary chest wall tumours, locally-invasive malignancies or metastatic lesions (4). The optimal approach to reconstruction is determined by the size, location and depth of the defect, viability of the surrounding tissue and prior operative procedures (5), because in case of neoplastic pathology it's mandatory to obtain oncologic margins not compromised and this could be result in large full-thickness defects (6), often resulting in a significant morbidity and mortality for the patient (3,(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…3 gezeigten, kombinierten "vertical/ transverse rectus abdominis muscle"-Lappen (V/TRAM) durchgeführt werden. Bei exulzeriertem Mammakarzinom (a) erfolgte in diesem Fall zunächst die Thoraxwandresektion und daraufhin die Rekonstruktion mit gestieltem VRAM/TRAM-Ankerlappen [22,24], gestielt an den superioren epigastrischen Gefäßen. Zusätzlich erfolgte eine modifizierte Abdominoplastik mit Nabelneueinpflanzung (b) zum Verschluss des Hebedefekts.…”
Section: Operative Möglichkeitenunclassified
“…Die wenigen zu diesem Thema vorliegenden Untersuchungen konnten belegen, dass auch ausgedehnte Eingriffe, wie Thoraxwandresektionen und -rekonstruktionen die Lebensqualität der Patienten verbessern können. Knapp die Hälfte der in palliativer Absicht operierten Patienten lebte nach der Operation noch länger als 2 Jahre [22]. Die operativen Therapien sollen für den Patienten eine kurze Hospitalisierungsdauer mit rascher Rekonvaleszenz beinhalten, um die restliche Lebenszeit ohne Wundkomplikationen, mög-lichst im heimischen Umfeld verbringen zu können.…”
Section: Bisherigeunclassified
“…5) Moreover, data available in the literature report mainly on survival, recurrence and metastasis rates whereas reports focused on the impact on pulmonary function are scarce. 6,7) As well, no follow-up studies report about pulmonary assessment after G-Tex reconstruction.…”
Section: To the Editormentioning
confidence: 99%